CARRYING OUT ROOMBOY DUTIES AT THE HOUSEKEEPING DEPARTMENT AT THE NOVOTEL PEKANBARU HOTEL - Widanto "; Andi Moh Rifiyan Arief (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Hotels are one type of accommodation that uses part or all of the building to provide accommodation services, food and drink and other services that are managed commercially. A hotel certainly has a department that has a big role, one of which is the Housekeeping Department. Housekeeping Department is part of the hotel department responsible for cleanliness, tidiness, and comfort of guest rooms, public areas, restaurants, bars and other outlets. In the Housekeeping Department there are sections that support their duties including the room boy who has the role of creating a clean, neat and complete room in order to get a good impression for guests who are staying and visiting. As for one of the hotels in Pekanbaru that has the best service, especially in the Housekeeping Department in order to increase guest satisfaction, the Hotel Novotel Pekanbaru is one of the 4-star standard hotels in Pekanbaru. The purpose of this study is to find out how to work and what are the obstacles of implementing the Roomboy Housekeeping department's duties at the Novotel Pekanbaru hotel. In writing this paper, the author uses qualitative data analysis techniques, namely analyzing, describing and summarizing various conditions, situations from various data collected in the form of results from interviews and observations about the problems being investigated that occur in the field. Keywords: hotel, housekeeping department, roomboy